2013
DOI: 10.1002/anie.201307897
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Assisted Self‐Assembly: Alignment, Placement, and Arrangement of Two‐Dimensional Mesostructured DNA–Silica Platelets

Abstract: Highly ordered hierarchical biomolecule-inorganic structures, such as bone, dentine, eggshell, and marine mollusc shells, are ubiquitous in nature. [1] The artificial organization of nature-inspired, biomolecule-templated hierarchical inorganic materials is a key challenge in enabling many nanotechnological applications.[2] "Bottom-up" self-assembly is a widely applied strategy for synthesizing and fabricating ordered hierarchical/multilevel spatial structures or morphologies from components ranging from nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…Che and Shinkai pioneered the field of silicification of nucleic acids. Introducing co‐interacting reagents was a major breakthrough, which led to the various applications, including chiral optical materials . Recently, Grass and co‐workers showed that silica is a perfect environment to preserve nucleic acids for the information storage and biomedical purposes .…”
Section: Figurementioning
confidence: 99%
“…Che and Shinkai pioneered the field of silicification of nucleic acids. Introducing co‐interacting reagents was a major breakthrough, which led to the various applications, including chiral optical materials . Recently, Grass and co‐workers showed that silica is a perfect environment to preserve nucleic acids for the information storage and biomedical purposes .…”
Section: Figurementioning
confidence: 99%
“…27 (2) Bottom-up methods take advantage of the selforganizing, self-assembly properties of certain nanomaterials such as nano-silica. 95e101 In molecular imprinting, researchers use templates such as viruses, 102 DNA, 103 plant-based constituents such as diosgenin from wild yam, 99 or toxic chemicals such as bisphenol 104,105 anchored onto larger silica surfaces. They then add silica precursors in solution.…”
Section: Figure 2 Top Down and Bottom Up Manufacturing Strategies Formentioning
confidence: 99%
“…[8] Die Selbstorganisation von Templaten ermçglicht die Kontrolle über Abmessungen, Periodizität und Struktur und bietet Zugang zu vielen neuen Nanomaterialien. Das Templat selber kann hart, wie Kohlenstoff [9] und Siliciumoxid, [10] sein oder ein weiches Templat, [11] wie Biomoleküle [12] und Polymere. [13] Dabei müssen weiche Template dazu fähig sein, sich zu transferierbaren Überstrukturen zu organisieren.…”
Section: Introductionunclassified